Jewish Motherhood/Unmotherhood. Issue 1 (1st August 2018) - Lightman, Sarah; Steinberg, Emily
Jewish Motherhood/Unmotherhood is an autobiographical, ongoing, multi-media project by artists Sarah Lightman and Emily Steinberg. Jewish Motherhood/Unmotherhood includes paintings, drawings, animated films and comics, and explores the intense sociocultural pressures within the Jewish community surrounding motherhood. Motherhood is one of the central tenets of Jewish life for women. But what if your experience of being a mother is not meaningful or enjoyable? What if you can't/won't have children? A culture of expectation, shame and secrecy surround women on all sides of the Jewish motherhood/unmotherhood spectrum. This project explores Sarah's experiences of having, and Emily's experience of not having, children.